2007
DOI: 10.1590/s1413-86702007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of persistent proteinuria in stable HIV/AIDS patients and its association with HIV nephropathy

Abstract: Human immunodeficiency virus (HIV)-related glomerular disease is a cause of end-stage renal disease, though there is no recent data from Brazil concerning this syndrome. Persistent proteinuria (PPt) is the main marker for glomerular disease, especially levels above 1.5 g. We examined the prevalence of and associated risk factors for PPt, along with the prevalence of HIV-associated nephropathy (HIVAN) among AIDS patients. We interviewed 411 patients who were attended at the HIV/AIDS section of the Clinical Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
4
0
5
Order By: Relevance
“…[13] Moreover, lower number of patients in our study were on cART (65.9%), compared to studies from the United States (77%) and Brazil (92%). [1920] We have also reported a comparatively higher prevalence of dipstick proteinuria in this study (29%). This is comparable to two large studies from the United States reporting proteinuria of 29.8% and 32%.…”
Section: Discussionsupporting
confidence: 71%
“…[13] Moreover, lower number of patients in our study were on cART (65.9%), compared to studies from the United States (77%) and Brazil (92%). [1920] We have also reported a comparatively higher prevalence of dipstick proteinuria in this study (29%). This is comparable to two large studies from the United States reporting proteinuria of 29.8% and 32%.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the recent Kidney Disease Initiative and Global Outcome (KDIGO) CKD Guidelines recommend, in individuals with proteinuria by dipstick, to perform confirmatory protein quantification within 3 months [24]. Defining proteinuria as a positive urine dipstick test on two occasions [25] could have reduced the false positive rate in our study, but probably at the expense of an even higher false negative rate.…”
Section: Discussionmentioning
confidence: 90%
“…[24] Prevalence of HIVAN in kidney biopsy series outside India have reported prevalence of HIVAN ranging from 0% to 83% [Table 2]. [7252627282930313233] HIVAN has been consistently and frequently reported in studies from North America, Western Europe and African countries. However, studies from Italy and Thailand have shown complete absence of this entity.…”
Section: Discussionmentioning
confidence: 99%